The ROI of human capital : measuring the economic value of employee performance - Fitz-enz, Jac (AMACOM, 2009)
The lifeblood of any business enterprise is its people. Yet it wasn't until the publication of the groundbreaking book The ROI of human capital that there was a reliable way to quantify the contributions of people to corporate profit. Completely updated with new metrics, the book shows executives and HR professionals how to gauge human costs and productivity at three critical levels: organizational (contributions to corporate goals), functional (impact on process improvement), human resources management (value added by five basic HR department activities).
Keywords: Human capital.; Productivity accounting.; Labor economics.; elektronické knihy; electronic books